Validation of an enzyme-linked immunosorbent assay for measurement of feline haptoglobin. (May 2016) - Stiller, Jenny; Jasensky, Anne-Katherine; Hennies, Mark; Einspanier, Ralf; Kohn, Barbara
Haptoglobin is a positive moderate acute phase protein (APP) in cats. Measurement of haptoglobin can be used in the diagnosis, prognosis, and monitoring of systemic inflammatory disease, especially by creating profiles with major APPs. The aim of our study was to validate a sandwich enzyme-linked immunosorbent assay (ELISA) for measurement of feline haptoglobin. The validation included an assessment of precision, accuracy, detection limit, method comparison with a spectrophotometric assay, and evaluation of the overlap performance. The concentration of haptoglobin was measured in serum from 27 healthy and 23 sick cats. The coefficients of variation were 2.5–4.7% for intra-assay variability and 7.1–11.6% for interassay variability. The ratio of observed to expected dilutional parallelism of 4 serum samples was 108.1–118.4%. The ratio of observed to expected spike recovery of 4 serum samples was 90.8–94.0%. The lower detection limit was 0.19 g/L. Method comparison revealed a positive correlation ( r s = 0.949, P < 0.0001) and a proportional bias between the methods of −38.9%. Agreement between the methods was not clinically acceptable. Overlap performance of the ELISA was deemed satisfactory. The sandwich ELISA measures feline haptoglobin with an analytical and overlap performance acceptable for clinical purposes. Given the observed bias, the ELISA cannot be used interchangeably with the spectrophotometric assay.